The films of Konrad Wolf : archive of the revolution - Powell, Larson, 1960- (Rochester, New York : Camden House, 2020)
"This is the first book in any language on the films of Konrad Wolf (1925-1982), East Germany's greatest filmmaker, and puts Wolf in a larger European filmic and historical context"--
Introduction : shadowlines : viewing Wolf's films -- Einmal ist keinmal (1955) -- Genesung (1956) -- Lissy (1957) -- Sonnensucher (1958/1972) -- Sterne (1959) -- Professor Mamlock (1961) -- The Minor Films: Leute mit Flügeln (1960), Der kleine Prinz (1966/1972), Busch singt (1982) -- Der geteilte Himmel (1964) -- Ich war neunzehn (1968) -- Goya (1971) -- Der nackte Mann auf dem Sportplatz (1974) -- Mama, ich lebe (1977) -- Solo Sunny (1980).
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Wolf, Konrad, -- 1925-1982 -- Criticism and interpretation; Wolf, Konrad, -- 1925-1982; Motion pictures -- Germany (East) -- History; Cinéma -- Allemagne (Est) -- Histoire; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion pictures; Germany (East); Aesthetic Conscience; Antifascist Films; Archive of the Revolution; Brecht; East Germany's Greatest Filmmaker; European Filmic; Everyday Life; Fassbinder; Filmic Forms; Films of Konrad Wolf; Generic References; German-Language Films; Historical Context; Konrad Wolf; Musical; Political Function; Tarkovsky; Wajda; Criticism, interpretation, etc; History